Globular Glial Mixed Four Repeat Tau and TDP‐43 Proteinopathy with Motor Neuron Disease and Frontotemporal Dementia. (19th May 2015) - Takeuchi, Ryoko; Toyoshima, Yasuko; Tada, Mari; Tanaka, Hidetomo; Shimizu, Hiroshi; Shiga, Atsushi; Miura, Takeshi; Aoki, Kenju; Aikawa, Akane; Ishizawa, Shin; Ikeuchi, Takeshi; Nishizawa, Masatoyo; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) may be accompanied by frontotemporal dementia (FTD). We report a case of glial mixed tau and TDP‐43 proteinopathies in a Japanese patient diagnosed clinically as having ALS‐D. Autopsy revealed loss of lower motor neurons and degeneration of the pyramidal tracts in the spinal cord and brain stem. The brain showed frontotemporal lobar degeneration (FTLD), the most severe neuronal loss and gliosis being evident in the precentral gyrus. Although less severe, such changes were also observed in other brain regions, including the basal ganglia and substantia nigra. AT8 immunostaining revealed that predominant occurrence of astrocytic tau lesions termed globular astrocytic inclusions (GAIs) was a feature of the affected regions. These GAIs were Gallyas‐Braak negative. Neuronal and oligodendrocytic tau lesions were comparatively scarce. pS409/410 immunostaining also revealed similar neuronal and glial TDP‐43 lesions. Interestingly, occasional co‐localization of tau and TDP‐43 was evident in the GAIs. Immunoblot analyses revealed band patterns characteristic of a 4‐repeat (4R) tauopathy, corticobasal degeneration and a TDP‐43 proteinopathy, ALS/FTLD‐TDP Type B . No mutations were found in the MAPT or TDP ‐43 genes. We consider that this patient harbored a distinct, sporadic globular glial mixed 4R tau and TDP‐43 proteinopathy associated with motor neuron disease and FTD.